GEOINFORMATION SUPPLY FOR CREATION AND ANALYSIS OF THE MODEL OF HYDROACMUNICATION ELECTRICITY: Array - Yevdokimov, A.; Kasyanov, D.; Ievleva, O. (Municipal economy of cities (Technical science), 2019)
The main aspects of creating and analyzing the digital model of the hydroaccumulating power plant are presented. Creation and analysis of the model of the hydroaccumulating power plant was carried out with the help of CAD and GIS technologies. In this section, safety and prevention of accidents are considered as the main and interconnected activities of a pumped storage power plant and its possible development. The realization of the investigated measures will promote optimization of work and increase of efficiency of operation and rational use of resources of the hydroelectric power plant. On the basis of research, model generation and analysis of the hydropower plant, the necessary initial data were identified, the main application of such a model by means of GIS. Several examples of the causes of emergencies were considered and the importance of organizing actions by means of GIS was considered, first of all, to prevent accidents and minimize the consequences of the accident on the environment and population. On the basis of the work, the first step was taken to create an effective model of the hydroaccumulating power plant by means of GIS, which would allow analyzing the introduction of new systems for the efficiency and safety of the object. The object of the study is the hydroelectric power station "Kyiv HPS". The subject of the study is geoinformation modeling and analysis of a hydroelectric power station in order to prevent accidents and environmental accidents. The research methods used are geoinformation modeling, geoinformation analysis, statistical analysis. The paper deals with the issues of geoinformation modeling and analysis of the hydroaccumulation plant, statistical analysis of the risk of emergencies.